Reliability of Peak Running Velocity Obtained on the Track Field in Runners of Different Performance Levels - Manoel, Francisco de Assis; Peserico, Cecília Segabinazi; Machado, Fabiana Andrade (Frontiers in Physiology, 2021)
The aim of this study was to verify the reliability of peak running velocity obtained on the track field (Vpeak_TF) in runners of different performance levels. 39 male endurance runners were divided into two groups: trained runners (TR; n = 22; 10-km time running performance of 35.2 ± 1.7 min), and recreational runners (RR; n = 17; 10-km time running performance of 51.3 ± 4.8 min). They performed three maximal incremental running tests on the official track field (400 m), with an interval of 1 week between trials to determine the reliability of Vpeak_T. The Vpeak_TF showed high reliability, presenting an intraclass correlation coefficient and coefficient of variation of 0.97 and 1.28%, and 0.90 and 1.24% for TR and RR, respectively. Both TR and RR showed lowest bias and limits of agreement between test and retest (Vpeak_TF1 and Vpeak_TF2). In addition, there was no statistical test-retest difference for Vpeak_TF. In addition, the HR and RPE submaximal values were reliable for both TR and RR. Therefore, the Vpeak_TF showed high reliability in both TR and RR. These findings reinforce that the protocol for determining Vpeak_TF, using increments of 1 km h–1 every 3 min is reliable regardless of the performance level of the runners.